A new species of furciseta (Diptera, Ctenostylidae) from the Brazilian Amazon - Câmara, Josenir Teixeira (Zootaxa, 2020)
Furciseta Aczél, 1956 [type species: F. plaumanni (Hennig, 1952)] was described as a monotypic genus from southern Brazil and is known only from the type material. Herein, F. hyalipennis n. sp. is described and illustrated based on three males and one female collected in the Brazilian states of Amazonas and Maranhão. An illustrated key to the two known species is presented. Copyright © 2013 Magnolia Press.